2015
DOI: 10.1212/wnl.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Associations of brain lesions at autopsy with polysomnography features before death

Abstract: Objective: To determine how sleep-disordered breathing, nocturnal hypoxia, and changes in sleep architecture in the elderly may be related to the development of the neuropathologic correlates of dementia.Methods: The Honolulu-Asia Aging Study is a prospective cohort study of Japanese American men in Honolulu, HI. We examined brain lesions at autopsy (Braak stage, neurofibrillary tangle and neuritic plaque counts, microinfarcts, generalized brain atrophy, lacunar infarcts, Lewy bodies [LBs], neuronal loss and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…However, oxygen desaturations (number of drops by ≥3% per minute) correlated strongly with smaller hippocampal and parietal white matter estimates. Consistent with these desaturation findings, in the Honolulu-Asia Aging Study, lower oxygen saturation levels predicted post-mortem autopsy findings of microinfarcts, Lewy bodies, and gliosis and neuronal loss by approximately 6 years [101]. These results converge with Yaffe et al’s [102] finding that oxygen desaturations were predictive of developing mild cognitive impairment or dementia whereas arousals and other measures of sleep fragmentation were not predictive.…”
Section: Neuroimaging Studies In Patients With Sleep Disordered Breatsupporting
confidence: 68%
“…However, oxygen desaturations (number of drops by ≥3% per minute) correlated strongly with smaller hippocampal and parietal white matter estimates. Consistent with these desaturation findings, in the Honolulu-Asia Aging Study, lower oxygen saturation levels predicted post-mortem autopsy findings of microinfarcts, Lewy bodies, and gliosis and neuronal loss by approximately 6 years [101]. These results converge with Yaffe et al’s [102] finding that oxygen desaturations were predictive of developing mild cognitive impairment or dementia whereas arousals and other measures of sleep fragmentation were not predictive.…”
Section: Neuroimaging Studies In Patients With Sleep Disordered Breatsupporting
confidence: 68%
“…Of note, in a prospective study higher nocturnal oxygenation during REM sleep was associated with less gliosis and neuronal loss in the locus coeruleus 65 . Major depression, on the other hand, is associated with exaggerated REM sleep qualities and deficiency in monoamine activity .…”
Section: Of All Psychiatric Disorders the Evidence For Increased Prementioning
confidence: 89%
“…An independent association between excessive daytime somnolence and cognitive impairment has been demonstrated and several prospective studies have shown that excessive daytime somnolence is associated with an increased risk of cognitive decline and dementia 14 . In a prospective cohort study (The Honolulu-Asia Aging Study), lower nocturnal oxygenation and reduction in SWS nREM sleep were associated with the development of microinfarcts and brain atrophy 65 . Conversely, men with longer SWA sleep showed slower cognitive decline 65 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Apnea Positive Pressure Long-term Efficacy Study (APPLES), middle age patients, with an average age of 52 years, showed a mild increase in cognitive function with continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea [31••]. Recent studies have identified nocturnal hypoxia and decreased slow-wave sleep as risk factors for gray matter changes, but not for Alzheimer's disease or Lewy body dementia [32]. To date, evidence regarding the impact of obstructive sleep apnea treatment on cognitive function in the elderly is inconclusive.…”
Section: Memory Impairmentmentioning
confidence: 99%